Oliceridine for the Management of Moderate to Severe Acute Postoperative Pain: A Narrative Review - Daksla N; Wang A; Jin Z; Gupta A; Bergese SD (Dove Medical Press, 2023)
Neil Daksla,1 Ashley Wang,1 Zhaosheng Jin,1 Abhishek Gupta,1 Sergio D Bergese1,2 1Department of Anesthesiology, Stony Brook University Health Science Center, Stony Brook, NY, 11794-8480, USA; 2Department of Neurosurgery, Stony Brook University Health Science Center, Stony Brook, NY, 11794-8480, USACorrespondence: Sergio D Bergese, Department of Anesthesiology, Stony Brook University School of Medicine, Health Sciences Center, Level 4, Room 060, Stony Brook, NY, 11794, USA, Tel +1 631 444-2979, Fax +1 631 444-2907, Email sergio.bergese@stonybrookmedicine.eduAbstract: Despite current advances in acute postoperative pain management, prevalence remains high. Inadequate treatment could lead to poor outcomes and even progression to chronic pain. Opioids have traditionally been the mainstay for treatment of moderate to severe acute pain. However, their use has been associated with opioid-related adverse events (ORAEs), such as respiratory depression, sedation, nausea, vomiting, pruritus, and decreased bowel motility. In addition, their liberal use has been implicated in the current opioid epidemic. As a result, there has been renewed interest in multimodal analgesia to target different mechanisms of action in order to achieve a synergistic effect and minimize opioid usage. Oliceridine is a novel mu-opioid receptor agonist that is part of a new class of biased ligands that selectively activate G-protein signaling and downregulate β-arrestin recruitment. Since G-protein signaling has been associated with analgesia while β-arrestin recruitment has been associated with ORAEs, there is potential for a wider therapeutic window. In this review, we will discuss the clinical evidence behind oliceridine and its potential role in acute postoperative pain management. We have systematically searched the PubMed database using the keywords oliceridine, olinvyk, and trv130. All articles identified were reviewed and evaluated, and all clinical trials were included.Keywords: postoperative pain, opioids, multimodal analgesia, opioid-related adverse events, biased agonism